If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4 = 15x + 8 Reorder the terms: 4 + 6x = 15x + 8 Reorder the terms: 4 + 6x = 8 + 15x Solving 4 + 6x = 8 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 4 + 6x + -15x = 8 + 15x + -15x Combine like terms: 6x + -15x = -9x 4 + -9x = 8 + 15x + -15x Combine like terms: 15x + -15x = 0 4 + -9x = 8 + 0 4 + -9x = 8 Add '-4' to each side of the equation. 4 + -4 + -9x = 8 + -4 Combine like terms: 4 + -4 = 0 0 + -9x = 8 + -4 -9x = 8 + -4 Combine like terms: 8 + -4 = 4 -9x = 4 Divide each side by '-9'. x = -0.4444444444 Simplifying x = -0.4444444444
| 2/4(x-16)=-6 | | 18x-24-10x-15=17 | | 3m+8m=6m | | 6x-8+3x=12x+8 | | 2x+10+2x-22=3x-18 | | .4(x+2.4)=2.96 | | (4x+9)+(2x-12)= | | 27x-36-14x+63=300 | | 4.5(x-9)=-25 | | 19-7m=14-6m | | 3/16-1/4 | | 5t^2+t=42 | | 2x-4(3x+1)-5= | | 3x-10+x+15=25 | | 11x-14=3x-14 | | x-1/x^3+2x | | N+17=14+3 | | -6+-12+-10+25= | | (x-3)squared=25 | | 3x^2+9=x^2+27 | | (x-3)/2=25 | | 6x^3-x^2-2x=0 | | 5x/2+12=-8 | | 5g+2g=7g | | 6-7g=-8 | | 6x+10y=50 | | x^3-9x^2+22x-15=0 | | 3n^2-5=0 | | 34-3w=25 | | 8x(8x-7)+-8x(9x-8)= | | 4-1/2 | | -50+87x=-75x^2-8x |